Understanding the mechanisms that facilitate specificity, not redundancy, of chemokine‐mediated leukocyte recruitment - Dyer, Douglas P. (Immunology, 2020)
Chemokines (chemotactic cytokines) and their receptors are critical to recruitment and positioning of cells during development and the immune response. The chemokine system has long been described as redundant for a number of reasons, where multiple chemokine ligands can bind to multiple receptors and vice versa. This apparent redundancy has been thought to be a major reason for the failure of drugs targeting chemokines during inflammatory disease. We are now beginning to understand that chemokine biology is in fact based around a high degree of specificity, where each chemokine and receptor plays a particular role in the immune response. This specificity hypothesis is supported by a number of recent studies designed to address this problem. This review will detail these studies and the mechanisms that produce this specificity of function with an emphasis on the emerging role of chemokine–glycosaminoglycan interactions.